Sensitive Determination of Acyclovir in Biological and Pharmaceutical Samples Based on Polymeric Film Decorated with Nanomaterials on Nanoporous Glassy Carbon Electrode. Issue 13 (1st January 2018) - Hamtak, Maryam; Fotouhi, Lida; Hosseini, Morteza; Dorraji, Parisa Seyed
Abstract : In the present study, a new sensor was designed by casting of multi-walled carbon nanotubes (MWCNTs) and TiO2 nanoparticles (TiO2 NPs) into the polymeric matrix, which polymerized in the nanoporous glassy carbon electrode. The morphological characterization of the new electrode was examined by field emission scanning electron microscopy. The performance of the electrode was demonstrated by applying it to the analytical determination of acyclovir concentration by differential pulse anodic stripping voltammetry. The oxidation of acyclovir has a better result on the modified electrode because of the synergistic effect of nanoporous structure glassy carbon electrode and polymeric film and MWCNTs+TiO2 NPs. The measurement of acyclovir on the fabricated electrode has the best response under the conditions of 0.10 mol cm −3 phosphate buffer solution (pH 7.0), accumulation potential of 0.6 V, and accumulation time of 180 s. Under the optimized conditions, the response of this electrode to the concentration of acyclovir was a single linear range ranges from 0.03 to 1.0 μmol dm −3 with a detection limit of 0.01 μmol dm −3 . Selective detection of acyclovir in the presences of ascorbic acid, dopamine and guanine, could be possible. The measurement of acyclovir concentrations in human fluid and tablet samples demonstrated electrode applicability.